MEDIATED DEATH AND DIGITAL MARTYRDOM: ETHICAL CONSIDERATIONS FOR VISUAL SOCIAL MEDIA RESEARCHERS - Lewis, Kelly Marie (AoIR Selected Papers of Internet Research, 2018)
The digital mediation of visual content depicting death and martyrdom as a trope of resistance and contestation is increasingly employed within social media platforms by transnational activist cultures and popular social movements. I refer to this phenomenon as ‘digital martyrdom’. The emergence of digital martyrdom, and its memetic circulation within visual social media platforms, points to the materialisation of a new, affective and ritualised protest dynamic. Through which posthumous visuals become diffused, reappropriated and politicised within global publics. This raises new ethical implications and moral dilemmas for digital and visual social media researchers, and requires more reflexive and critical thought beyond established ethical considerations. Necessarily, this paper raises ethical questions and provocations for digital and visual social media researchers in relation to the design, collection, presentation and publishing of academic work in the context of death and posthumous imagery online. The questions presented in this paper have emerged out of a systematic study of this phenomenon, with a particular focus on case studies drawn from the Middle East, the United States and Europe. This paper argues that digital and visual social media research in this field merits specific ethical considerations and amplified scholarly deliberation. This is of particular importance for visual social media research that extends beyond a Western context and considers the cross-cultural, transnational dimensions of digital activism.